2012
DOI: 10.2224/sbp.2012.40.5.875
|View full text |Cite
|
Sign up to set email alerts
|

Active Seniors and Mobile Phone Interaction

Abstract: In this study we analyzed the interaction between active seniors and mobile phone use. Results were obtained from a survey. Participants were 165 active seniors enrolled in university programs for seniors, most of whom owned a mobile phone and used it for basic functions such as making calls, creating a contact list, checking the time, and sending text messages. The mobile phone did not have a social expansion function (that is, to extend their social networks) for these people; but it did provide them with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Plaza et al 2011). Specifically, one study has shown that older age groups understand mobile phones as devices that provide access to social support by their social network members (Martinez-Pecino, Lera, and Martinez-Pecino 2012). In another study, researchers suggested that by using a mobile phone, older age groups extend their communication with their support networks (Petrovčič et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Plaza et al 2011). Specifically, one study has shown that older age groups understand mobile phones as devices that provide access to social support by their social network members (Martinez-Pecino, Lera, and Martinez-Pecino 2012). In another study, researchers suggested that by using a mobile phone, older age groups extend their communication with their support networks (Petrovčič et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, ICTs fostered social connections with family, friends and new acquaintances ( Straka and Clark, 2000 ; Pfeil et al, 2009 ; Ballantyne et al, 2010 ; Khvorostianov et al, 2011 ; Blažun et al, 2012 ; Cornejo et al, 2012 ; Garattini et al, 2012 ; Nimrod, 2012 ; Pecino et al, 2012 ; Tsai et al, 2012 , 2015 ; Winstead et al, 2012 ; Cotten et al, 2013 ; Jimison et al, 2013 ; Larsson et al, 2013 ; Arthanat et al, 2014 ; Huang and Hsu, 2014 ; Osmanovic and Pecchioni, 2015 ; Waycott et al, 2015 ; Delello and McWhorter, 2016 ; Ivan and Hebblethwaite, 2016 ; Melenhorst et al, 2016 ; Papa et al, 2016 ; Pimentel et al, 2016 ; Xu et al, 2016 ; Sims et al, 2017 ; Barbosa Neves et al, 2018 ; Czaja et al, 2018 ; Nimrod and Ivan, 2019 ; Zaine et al, 2019 ; Lyu and Sun, 2020 ). ICT use was associated with greater emotional and/or social support ( Tsai et al, 2010 ; Woodward et al, 2010 ; Tsai and Tsai, 2011 ; Czaja et al, 2018 ) and social engagement (going out and hobbies) ( Kim et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Activities involving family connections were reported as being performed more frequently than those involving general social connection, leisure, health management, shopping, finances ( Arthanat et al, 2014 ) or even obtaining new information ( Sims et al, 2017 ). In turn, research indicates ICTs helped strengthen communication between older adults and their family and friends ( Straka and Clark, 2000 ; Pfeil et al, 2009 ; Ballantyne et al, 2010 ; Khvorostianov et al, 2011 ; Pecino et al, 2012 ; Cotten et al, 2013 ; Jimison et al, 2013 ; Larsson et al, 2013 ; Huang and Hsu, 2014 ; Tsai et al, 2015 ; Delello and McWhorter, 2016 ; Ivan and Hebblethwaite, 2016 ; Melenhorst et al, 2016 ; Papa et al, 2016 ; Pimentel et al, 2016 ; Barbosa Neves et al, 2017 ; Sims et al, 2017 ; Czaja et al, 2018 ; Zaine et al, 2019 ). ICTs commonly reinforced in-person meetings and complemented offline communication with family, friends and new acquaintances ( Pfeil et al, 2009 ; Larsson et al, 2013 ; Lelkes, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers blocking older adults to participate in online learning activities appear to be the same as those that prevent them from using computers in general (Notess and Lorenzen-Huber 2007). Individuals that make small or no use of technology are at risk of social exclusion and loss of participation in and interaction with society (Pecino et al 2012). Advanced age is often associated with the phenomenon of the "digital divide" (Rice and Katz 2003;Vicente and López 2006), which induces inequalities concerning access, use and intensity of use of ICTs (Jackson et al 2008; Torres Diaz and Moro 2011).…”
Section: E-learning For Older Adultsmentioning
confidence: 99%